PENDAMPINGAN PEMBUATAN PUISI PADA GURU BAHASA INDONESIA DI MIS KECAMATAN SOSA KABUPATEN PADANG LAWAS - Nurhayati Siregar; Derpina Sari Nasution; Emma Salamah Hasibuan; Misra Cahaya Hasibuan; Rina Melani; Netti Hasibuan; Rodiatam Mardiah (Jurnal Pengabdian Masyarakat Multidisiplin, 2023)
The purpose of this Community Service Research is to apply poetry by determining the theme, taste, tone, mandate. The research used there are two activities, namely Traditional Scouting and Outdoor Activity. Traditional Scouting activities are carried out through 5 (five) methods, namely orientation, workshops, games, and mentoring. While outdoor activities are carried out through methods, namely: practices that are implemented indoors. The method used is training in the form of theory and practice, the material presented is in the form of theory, while the practice is in the form of role playing and games. The expected results of the teacher are even better in making poems by including themes, tones, flavors, mandates.